Some aspects of the metabolism of the catecholamines and 5 - hydroxytryptamine in the brain - Pullar, Ian Alexander (The University of Edinburgh, 1971)
An investigation of several aspects of the metabolism of the biogenic amines, dopamine, noradrenaline, and 5—hydroxytryptamine in the central nervous system, has been undertaken. The work was directed mainly to a quantitative study of the catabolites of the amines in human cerebrospinal fluid (c.s.f.) in order to monitor their turnover in the central nervous system in various clinical conditions. Of the catabolites considered, 3-methoxy-4-hydroxyphenylacetic acid (homovanillic acid, HVA} and 3,4-dihydroxyphenylacetie acid (DOPAC) derived from dopamine and 5-hydroxyindol-3-ylacetic acid (5-HIAA) from 5-hydroxytryptamine were specifically studied in relation to the therapy of parkinsonism with L-DOPA and the main cerebral catabolites of noradrenaline, 3-methoxy-4-hydroxyphenylethyleneglycol (MOPEG) and 3,4-dihydroxyphenylethyleneglycol (DOPKG), in relation tc various states of mental derangement. The latter investigation involved the development of methodology for the estimation of MOFEG and DOPEG in c.s.f.A short ancillary study was made of a possible role of the choroid plexus in the removal of the acidic metabolites of the biogenic amines from c.s.f.
A study of some aspects of the metabolism of the catecholamines and 5 - hydroxytryptamine in the brain